2003
DOI: 10.1021/jf021105j
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition of Champagnes from Chardonnay and Pinot Noir Vintages

Abstract: Nineteen phenolic compounds including hydroxybenzoic acids, hydroxycinnamic acids, flavonoids, phenolic alcohols, and phenolic aldehydes have been identified and quantified in two monovarietal champagnes, Chardonnay and Pinot Noir, by using a reverse-phase high-performance liquid chromatography (HPLC) system coupled with diode array detection. The identification of four hydroxycinnamic tartaric esters (caftaric, coutaric, fertaric, and 2-S-glutathionylcaftaric acids), two flavanonols (astilbin and engeletin), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 14 publications
6
78
4
Order By: Relevance
“…It has been found to play a key role in the regulation of plant growth, development and enhance plant vigour under biotic and abiotic stresses (Hayat et al, 2010). It is an important secondary metabolite in grape berries and plays an essential role in determining berry quality such as colour, flavour, astringency and bitterness (Chamkha et al, 2003). Preharvest foliar spray of 1.5 mM SA at pea stage and at veraison hastened berry maturity by 3 to 5 days, and produced less compact bunches alongside larger berries in contrast to the control (Champa et al, 2014b).…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…It has been found to play a key role in the regulation of plant growth, development and enhance plant vigour under biotic and abiotic stresses (Hayat et al, 2010). It is an important secondary metabolite in grape berries and plays an essential role in determining berry quality such as colour, flavour, astringency and bitterness (Chamkha et al, 2003). Preharvest foliar spray of 1.5 mM SA at pea stage and at veraison hastened berry maturity by 3 to 5 days, and produced less compact bunches alongside larger berries in contrast to the control (Champa et al, 2014b).…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…Each of the three main varieties contribute individual attributes to the finished wines, described as "finesse and elegance" for Chardonnay, "body" for Pinot noir, and "fruitiness and roundness" for Pinot Meunier (Jackson 2008). A sparkling wine made only from white grapes, and typically Chardonnay, is called a "Blanc de Blancs" and a sparkling wine made only from dark-skinned grapes, typically Pinot noir and/or Pinot Meunier grapes, is called a Blanc de Noirs (Chamkha et al 2003). Chenin blanc is grown in the Loire Valley of France for sparkling wine production, in particular for its naturally high acidity retention, and also in the Limoux region of France together with the more traditional variety of Mauzac (Robinson 2006).…”
Section: Grape Varietymentioning
confidence: 99%
“…A general guideline is the warmer the sparkling wine producing region, the earlier the grapes need to be harvested to ensure low pH and high acidity levels, as sparkling wines with higher pH and lower acidity levels tend to develop more quickly and are more likely to display more overt fruit flavors and less complexity (Zoecklein 2002). Variation in total phenolic content of Pinot noir and Chardonnay Champagnes was found to be a function of the vintage; researchers concluded that abundant rain in 2001 diluted flavor compounds relative to the 2000 vintage (Chamkha et al 2003).…”
Section: Climate and Soil Factorsmentioning
confidence: 99%
“…Marzouk and Kassem (2011) and Ahmed et al (2015) found that Cluster and berry weight as well as vine yield were improved by all sprayed chemicals, especially, salicylic acid . It is an important secondary metabolite in grape berries and plays an essential role in determining berry quality such as colour, berry size and bitterness Chamkha et al (2003). Also, Sabreen et al (2015) reported that the interaction applications between N at75 kg/feddan and treatment plants with chitosan at 0.10g/l gave the highest values of yield in summer squash fruits.…”
Section: Yield Cluster Weight 100 Berries Weight and Total Phenols mentioning
confidence: 99%